PEMANFAATAN MEDIA TIK TUTORIAL UNTUK REMEDIAL PADA PEMBELAJARAN ALAT UKUR DI SMP - Meitri Astuti; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
Remedial learning will be more effective if the process is done through media or other models which are different from the previous one. It is assumed that the use of media and methods will help the students to pass the score which has been determined. The purpose of this research is describing the result of the remedial learning, science process skills, character, activity, and attitude of the students. This research is done in junior high school 8 Bandar Lampung. The design of this research is one shot case study. N-gain score is used to analyze the data while paired sample t-test is implemented to examine the hypothesis. Based on the score gathered, it can be seen that the mean score of the students is middle score. The result of this research indicates that the learning process through ICT tutorial media can be used as an effort to improve the result of learning process in remedial learning.Pembelajaran remedial berjalan efektif jika pembelajaran remedial dilakukan dengan media atau model yang berbeda dari pembelajaran sebelumnya, sehingga membantu siswa memenuhi ketuntasan KKM. Penelitian bertujuan Mendeskripsikan hasil belajar remedial, KPS, karakter, aktifitas, dan sikap. Penelitian dilakukan di SMPN 8 Bandar Lampung. Desain penelitian One shot case study. Teknik analisis data hasil belajar menggunakan skor N-gain dan pengujian hipotesis menggunakan uji Paired Sample t-Test. Berdasarkan skor rata-rata N-gain diperoleh rata-rata hasil belajar dengan kategori sedang. Hasil tersebut mengindikasi-kan bahwa pembelajaran dengan menggunakan media pembelajaran berbasis TIK tutorial dapat digunakan sebagai upaya untuk meningkatkan hasil belajar siswa dalam pembelajaran remedial.Kata kunci: aktifitas, hasil belajar, keterampilan proses sains, media TIK tutorial, remedial.